PENGARUH DIGITAL MARKETING MELAULUI INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN MINUMAN KOPI DI KEDAI KOPI DUAPERTIGA - Mukammil, Mukammil; Astaman, Putra; Megawati, Megawati; Nurdin, Fadilah (Jurnal Riset Multidisiplin Agrisosco, 2025)
This study aims to examine the effect of digital marketing through Instagram, specifically focusing on the variables of content and timing, on consumer purchasing decisions at Kedai Kopi Duapertiga. The research employed a quantitative approach using multiple linear regression analysis to test the proposed hypotheses. The results show that the content variable has a positive and significant effect on purchasing decisions, with a significance value of 0.000 (p < 0.05). In contrast, the timing variable does not have a significant effect on purchasing decisions, with a significance value of 0.727 (p > 0.05). Simultaneously, the regression model consisting of content and timing significantly influences purchasing decisions, with a coefficient of determination (R²) of 0.308. This indicates that 30.8% of the variation in purchasing decisions can be explained by these two variables, while the remaining 69.2% is influenced by other factors outside the model.